Potential challenges of collaborative robot implementation in Vietnamese garment manufacturing - Nguyen, Kim Phung; Ma, Yoon Jin (IAES International Journal of Robotics and Automation (IJRA), 2024)
Collaborative robots (cobots) are a new significant technology in the integration of Industry 4.0 (I4.0) and Industry 5.0 (I5.0). Working alongside humans in open environments, cobots can boost safety and productivity. However, manufacturers are facing some potential challenges in adopting cobots, such as technological challenges, social problems, cost barriers, and labor issues. Vietnam has a great potential for outsourcing in the top supply chains for many famous fashion brands globally, with thousands of textile and garment factories. The purpose of this study was to explore potential challenges of cobot implementations in the context of Vietnam’s garment factories from factory employees’ perspectives. Data were collected from 29 garment factory managers in Vietnam. Findings revealed a rapid change in fashion trends and many unskilled workers may limit cobots’ flexibility, precision, and innovation. Furthermore, cobot implementation is affected by the cost of cobots, infrastructure upgrades, and risks of possible failure in deployment. Cobot firms, application partners, technology programmers, and manufacturers need to discuss how to maximize cobots’ benefits in diverse aspects of the garment manufacturing setting. These insights could boost the industry’s economy and sustainability.